Effects of xanthohumol and hop-prenylflavonoids on obesity and diabetes - Sofia Carreira Neves (2021)
Obesity, already recognized as a disease, and type 2 diabetes (T2D), which affects more than 400 million people, are increasing, influencing the quality of life and posing as a heavy burden on society, reinforcing the need for prevention and treatment of these diseases. Hop-prenylflavonoids have been studied as therapeutic agents in the treatment of obesity and T2D, due to their effects on oxidative stress, inflammation and metabolic diseases. Therefore, the aim of this review is to summarize and discuss the results obtained regarding the benefits of xanthohumol (XN), isoxanthohumol (IXN) and 8-prenylnaringenin (8PN) on obesity and T2D. For this, a search in pubmed database was made for these polyphenols and diseases, and related terms, without filters. This review summarizes the effects of XN, IXN and 8PN on obesity and T2D, with a particular focus on their mechanisms of action involving antioxidant and anti-inflammatory properties, mitochondrial uncoupling, binding to farnesoid X receptor, modulation of lipid profile and metabolism and effects on microbiota and angiogenesis. Prenylflavonoids seem to have multiple and overlapping mechanisms of action that may improve obesity and T2D. Nevertheless, more research on humans are necessary to confirm their potential use in the prevention or treatment of these pathologies.